VD_FINDINFO Pron / 2012 / 82 vom 16. April 2012 - VD Tribunal cantonal (2012)
DROIT D'OBTENIR UNE DÉCISION, MOTIVATION DE LA DÉCISION, RETARD INJUSTIFIÉ | 6 par. 1 CEDH, 29 al. 1 Cst., 319 let. c CPC (CH)